2018
DOI: 10.1002/ece3.4435
|View full text |Cite
|
Sign up to set email alerts
|

Ecological correlates of Himalayan musk deer Moschus leucogaster

Abstract: Himalayan musk deer (Moschus leucogaster; hereafter musk deer) are endangered as a result of poaching and habitat loss. The species is nocturnal, crepuscular, and elusive, making direct observation of habitat use and behavior difficult. However, musk deer establish and repeatedly use the same latrines for defecation. To quantify musk deer habitat correlates, we used observational spatial data based on presence–absence of musk deer latrines, as well as a range of fine spatial‐scale ecological covariates. To det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…In this study, musk deer pellets were most abundant in areas near water sources, indicating that distance to water source has importance in habitat selection by musk deer. These findings are also supported by study of Singh et al (2019), which concluded that topographical attributes including aspect, elevation, distance to water source, and slope were also discriminated by musk deer.…”
Section: A Csupporting
confidence: 63%
See 2 more Smart Citations
“…In this study, musk deer pellets were most abundant in areas near water sources, indicating that distance to water source has importance in habitat selection by musk deer. These findings are also supported by study of Singh et al (2019), which concluded that topographical attributes including aspect, elevation, distance to water source, and slope were also discriminated by musk deer.…”
Section: A Csupporting
confidence: 63%
“…Nep J Environ Sci (2021), 9(1), 21-28 https://doi.org/10.3126/njes.v9i1.37844 preferred by musk deer at Sagarmatha National Park whereas west and east in Kangchenjunga Conservation Area, north, north-west and south-west from Langtang National Park (Sharma et al, 2008) and recorded more in North-west (NW), south (S) and south-east (SE) slope at Annapurna Conservation Area (Aryal, 2006;Singh et al, 2019). Statistically, on applying the χ 2 -test showed a significant difference in musk deer signs distribution among different aspects at GCA (χ 2 = 15.25, at 95% level of significance, d.f.…”
Section: Tu-cdesmentioning
confidence: 99%
See 1 more Smart Citation
“…In water scarce environments, a small difference in moisture availability can make a difference in habitat quality. Such ecological expectations can also be inferred from the fact that forest cover is an important factor to KMD given their timid nature 30 and vegetation growth is largely influenced by moisture in dry environments [60][61][62][63][64] . These deer occur sparsely if there is inadequate dense vegetation cover (>40% crown cover) to hide within during the day 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In Api-Nampa Conservation Area, the slopes of 21-30º are highly preferred followed by slopes >40º by Musk Deer and avoid the slope of 0-10º (ANCA 2018). The study carried by Singh et al (2018b) recorded the majority of latrines of Musk Deer in the slope of 20-40º in ACA. Our study in ACA coincides with these two studies as the principally preferred slope lie at 20-30º and completely avoid the slopes of 0-10º and >41º.…”
Section: Discussionmentioning
confidence: 99%